2020
DOI: 10.1016/j.cell.2019.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics of the Cancer Cell Line Encyclopedia

Abstract: Highlights d Quantified the proteomes of 375 cell lines from diverse lineages in the CCLE d Correlated expression of proteins across many pathways d Downregulation of multiple protein complexes in microsatellite instability d Protein complexes associated with sensitivity to gene knockdown and mutation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
702
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 744 publications
(737 citation statements)
references
References 81 publications
34
702
1
Order By: Relevance
“…As described in the manuscript (Nusinow et al, 2020), the experiments were performed in a multiplex setup using a reagent named Tandem Mass Tags (TMT, Figure 1) that, at the start of the project, allowed 10 samples to be run in parallel on the mass spectrometer (McAlister et al, 2012(McAlister et al, , 2014Werner et al, 2012). Each sample in the data (the column names on supplemental table S2 of Nusinow et al, 2020) denotes which of the forty-two 10-plexes it was part of. In each 10-plex there were nine biological samples and one "bridge" sample that allowed normalization across plexes.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations
“…As described in the manuscript (Nusinow et al, 2020), the experiments were performed in a multiplex setup using a reagent named Tandem Mass Tags (TMT, Figure 1) that, at the start of the project, allowed 10 samples to be run in parallel on the mass spectrometer (McAlister et al, 2012(McAlister et al, , 2014Werner et al, 2012). Each sample in the data (the column names on supplemental table S2 of Nusinow et al, 2020) denotes which of the forty-two 10-plexes it was part of. In each 10-plex there were nine biological samples and one "bridge" sample that allowed normalization across plexes.…”
Section: Experimental Designmentioning
confidence: 99%
“…Details about the cell lines was provided as Supplementary Table S1 in Nusinow et al, 2020 and can also be found on the CCLE website. We used the internal CCLE nomenclature for cell line identification.…”
Section: Using the Normalized Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mRNA data of all 64 cell lines in the HPA show low expression of ACE2 in human small-cell lung cancer cells (SCLC-21H, Figure S2). However, ACE2 was not detected at the protein level in airway or lung tissues, indicating that the correlation between protein and transcription levels were widely varied [21]. Thus, limitations arise when predicting protein expression based only on mRNA expression levels.…”
Section: Expression Of Virus-associated Proteins On Epithelial Cells mentioning
confidence: 99%